2007
DOI: 10.1111/j.1527-3458.2007.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenosides: Are Any of them Candidates for Drugs Acting on the Central Nervous System?

Abstract: The last two decades have shown a marked expansion in the number of publications regarding the effects of Panax ginseng. Ginsenosides, which are unique saponins isolated from Panax ginseng, are the pharmacologically active ingredients in ginseng, responsible for its effects on the central nervous system (CNS) and the peripheral nervous system. Recent studies have shown that ginsenosides regulate various types of ion channels, such as voltage-dependent and ligand-gated ion channels, in neuronal and heterologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
136
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(139 citation statements)
references
References 132 publications
(204 reference statements)
3
136
0
Order By: Relevance
“…Cumulated research outcomes have indicated that identical and variable ginsenosides in these 2 herbs are possibly responsible for the comparable and distinct therapeutic effects between ginseng and sanqi [7] . Ginsenosides are triterpene saponins that have a common 4 ring hydrophobic steroid-like structure with sugar moieties attached mostly at the C-3, C-6, or C-20 position [8] . So far, more than 80 ginsenosides have been isolated from over 10 Panax taxa, and most of these are derived from 4 types of aglycones: protopanaxadiol, protopanaxatriol, oleanolic acid, and ocotillol [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Cumulated research outcomes have indicated that identical and variable ginsenosides in these 2 herbs are possibly responsible for the comparable and distinct therapeutic effects between ginseng and sanqi [7] . Ginsenosides are triterpene saponins that have a common 4 ring hydrophobic steroid-like structure with sugar moieties attached mostly at the C-3, C-6, or C-20 position [8] . So far, more than 80 ginsenosides have been isolated from over 10 Panax taxa, and most of these are derived from 4 types of aglycones: protopanaxadiol, protopanaxatriol, oleanolic acid, and ocotillol [9] .…”
Section: Introductionmentioning
confidence: 99%
“…7) Of constituents, ginsenosides have been reported to show biological activities, including anti-inflammatory, anti-fatigue, anti-stress, and anti-tumor activities. [8][9][10][11][12] The ginsenosides are classified as protopanaxadiols or protopanaxatriols. Orally administered protopanaxadiol-type and protopanaxatriol-type ginsenosides are metabolized to 20(S)-protopanaxadiol (PPD) via compound K and 20(S)-protopanaxatriol (PPT) via ginsenoside Rh1, respectively, by gut microbiota.…”
mentioning
confidence: 99%
“…Its perturbed neuronal Ca 2+ homeostasis is implicated in aging and age-related cognitive impairments [12] . Chen also showed that it could decrease the Aβ-induced elevation of intracellular calcium and stabilize microtubule integrity [18] .…”
Section: Mechanism Of Action Of Ginsenoside Rb1 On the Vgccs In Hippomentioning
confidence: 99%
“…Nifedipine is an L-type Ca 2+ channel inhibitor, ω-conotoxin GVIA is an N-type Ca 2+ channel inhibitor, and ω-agatoxin IVA is a P/Q-type Ca 2+ channel inhibitor [4][5][6][7][8][9] . Because the elevation of intracellular Ca 2+ levels ([Ca 2+ ] i ) caused by the excessive stimulation of Ca 2+ channels plays a key role in the excitotoxic damage of neurons, agents blocking the elevation of [Ca 2+ ] i by regulating Ca 2+ channels might have neuroprotective effects [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%